Peritoneal hydatid disease and pregnancy: report of three cases - Gamarra, Melvin (2015)
Three pregnant women with peritoneal hydatidosis are presented, who delivered at term, two of them vaginally without complications. We review current literature on potential complications associated with birth mode.